Forestry Utilization Policy: A Discourse Analysis - Azis Khan; Hariadi Kartodiharjo; Sudarsono Soedomo; Dudung Darusman (Jurnal Manajemen Hutan Tropika, 2010)
A series of discourse have constructed a social reality underlining the fact that Indonesian natural forestryexperienced a serious negative stigma. The stigma appeared due to its deforestation and forest degradation rate, likely un-ending multi-dimentional conflitcs, the increase of natural forest threat, the decrease of natural forest roles, and function in terms of social, economic and environment. This was addressed mainly to those of forestry utilization policies. This research has a look to analyse forestry utilization policies as an essential point, especially with regard to the discourse trend and to the frame of forestry stakeholder minds involving in the discourse which was focused on key policy miles stone and its implementation. It is considered to be essential since after much efforts of wiping the stigma off seemed to be unsuccesfully. The results indicated that there was a problem on stakeholders’ minds frame, which was considered to be a stagnant, especially on positioning and understanding forest utilization and sustainability. To cope with such a problem, it would need to improve at least four things, i.e: the link of science/knowledge-skills-policy, political interest, public participation, and actor networks. Improving the fourth could be an essential key for having another three.